Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1098/rspb.2004.3031
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for biased use of sperm sources in wild female giant cuttlefish ( Sepia apama )

Abstract: In species where females store sperm from their mates prior to fertilization, sperm competition is particularly probable. Female Sepia apama are polyandrous and have access to sperm from packages (spermatangia) deposited by males onto their buccal area during mating and to sperm stored in internal sperm-storage organs (receptacles) located below the beak. Here, we describe the structure of the sperm stores in the female's buccal area, use microsatellite DNA analyses to determine the genetic diversity of stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 28 publications
(38 reference statements)
4
46
0
3
Order By: Relevance
“…When D. simulans females were inseminated by both a D. simulans and a D. mauritiana male, females significantly switched between using sperm predominantly from the SR when the conspecific male mated first and from the spermathecae when the conspecific male mated second, thus biasing fertilization toward conspecific sperm (i.e., conspecific sperm precedence; Price 1997;Howard et al 2009) irrespective of mating order (Manier et al 2013b). Although this may seem unexpectedly sophisticated, biased use of sperm from different storage sites has also been demonstrated for the giant cuttlefish Sepia apama (Naud et al 2005), and there is evidence that females of the damselfly Calopteryx splendens xanthostoma similarly shift between different storage locations differing in composition of competing sperm dependent on the context of oviposition (Siva-Jothy andHooper 1995, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When D. simulans females were inseminated by both a D. simulans and a D. mauritiana male, females significantly switched between using sperm predominantly from the SR when the conspecific male mated first and from the spermathecae when the conspecific male mated second, thus biasing fertilization toward conspecific sperm (i.e., conspecific sperm precedence; Price 1997;Howard et al 2009) irrespective of mating order (Manier et al 2013b). Although this may seem unexpectedly sophisticated, biased use of sperm from different storage sites has also been demonstrated for the giant cuttlefish Sepia apama (Naud et al 2005), and there is evidence that females of the damselfly Calopteryx splendens xanthostoma similarly shift between different storage locations differing in composition of competing sperm dependent on the context of oviposition (Siva-Jothy andHooper 1995, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although the fertilization set has rarely been empirically identified (e.g., Manier et al 2010Manier et al , 2013aLü-pold et al 2012), it is likely to constitute all sperm occupying the female's sperm-storage organs, or the sperm "reservoir" in the case of many mammals. On the other hand, the fertilization set could be more expansive, additionally including sperm retained in the deposition site (e.g., Siva-Jothy andHooper 1995, 1996;Naud et al 2005), or it could be more restrictive, as in the sperm occupying a subset of multiple sperm-storage organs (Pitnick et al 1999;Manier et al 2010) or even a specific region within an organ. Here we introduce the term "fertilization bias" to refer to nonrandom deviations from the null expectation that sperm are used in direct proportion to their numerical representation in the fertilization set.…”
Section: Introductionmentioning
confidence: 99%
“…A field study on paternity in S. agama showed that, although the volumes of sperm present in the buccal receptacle and on the female's buccal surface (i.e. sperm forming the 'spermatangia' mass) were comparable, the majority of the fertilizing sperm came from the buccal surface rather than the buccal receptacle (Naud et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of egg capsules collected from the field demonstrate multiple paternity within egg capsules in this species (Buresch et al 2001), as well as in several other cephalopods including 2 loliginid squids, Loligo forbesi (Shaw & Boyle 1997) and L. vulgaris reynaudii (Shaw & Sauer 2004), and in the eggs of the Australian giant cuttlefish Sepia apama (Naud et al 2004). While these paternity studies suggest complex fertilization dynamics in loliginids and other cephalopods, changes in paternity over a relatively short period of time have been examined in only one trial for multiple clutch breeders (L. bleekeri, Iwata et al 2005) or in species that lay single eggs successively (S. apama, Naud et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of free ova in the ovary or oviduct was checked as a criterion for terminal maturation of females (Mangold 1987, Gauvrit et al 1997. In Sepia species, males deposit their spermatophores onto female buccal membranes during mating activity (Hanlon & Messenger 1996, Hanlon et al 1999, Naud et al 2005, Wada et al 2005. Therefore, the presence of spermatophores on female buccal membranes was checked to determine whether the female had mated or not.…”
Section: Measurement Of Specimensmentioning
confidence: 99%